Energy Landscapes and Structural Plasticity of Intrinsically Disordered Histones - Viegas, Rafael G. [UNESP]; Wu, Hao; Sanches, Murilo N. [UNESP]; Papoian, Garegin A.; Leite, Vitor B.P. [UNESP] (American Chemical Society (ACS), 2025)
Intrinsically disordered proteins (IDPs) are characterized by their lack of a stable 3D structure, enabling them to adopt multiple conformations and participate in various cellular processes. This study investigates the conformational dynamics of histone tails, specifically the H4 tail and the linker histone H1, focusing on the effects of post-translational modifications (PTMs) such as acetylation. Utilizing the energy landscape visualization method (ELViM), we projected the conformational space of wild type and acetylated forms of the H4 tail, revealing significant insights into their structural heterogeneity and preferential ensembles. This approach demonstrated that acetylation reduces the conformational heterogeneity of the H4 tail and introduces regions within the conformational space uniquely occupied by each form, which may correlate with specific biological functions. Furthermore, the conformational space of the linker histone H1 was analyzed, illustrating how its structural heterogeneity is influenced by nucleosome binding modes. This work highlights the critical role of conformational plasticity and PTMs in regulating the multifunctionality of IDPs, thereby enhancing our understanding of their contributions to chromatin dynamics and cellular regulation.